Propensity score-matched analysis comparing hippocampus-avoidance whole-brain radiotherapy plus simultaneous integrated boost with hippocampus‑avoidance whole-brain radiotherapy alone for multiple brain metastases-a retrospective study in multiple institutions - Xiaoliang Wang; Jinping Chen; Zhanquan Lei; Haihong Chen; Yufang Zhang; Gang Liu; Shaomin Li; Zhenhua Zheng; Hui Wang (BMC Cancer, 2023)
Abstract Background The optimal treatment for multiple brain metastases has been recently controversially discussed.This study was aimed to explore the feasibility of Hippocampus-Avoidance Whole-Brain Radiotherapy plus a simultaneous integrated boost (HA-WBRT + SIB) in patients with multiple brain metastases and assess tumor control in comparison with Hippocampus-Avoidance Whole-Brain Radiotherapy (HA-WBRT) alone for brain metastases. Methods In this study, 63 patients with multiple brain metastases (≥ 4 metastases) had undergone HA-WBRT + SIB between January 2016 and December 2020 in the observation group:HA-WBRT (30 Gy in 12 fractions, the maximum dose of the hippocampus ≤ 14 Gy) plus a simultaneous integrated boost (48 Gy in 12 fractions) for brain metastases.Overall Survival (OS), Median survival,intracranial control (IC = control within the entire brain), intracranial progression-free survival (iPFS) and adverse events were compared with the control group (a HA-WBRT retrospective cohort) by propensity score matching analysis. Results After 1:1 propensity score matching,there were 56 patients in each group (the observation group, the control group). OS, median survival and iPFS were significantly longer in the observation group (18.4 vs. 10.9 months, P<0.001), (13.0 vs. 8.0 months, P<0.001), (13.9 vs.7.8 months, P<0.001). In comparison of 1-year-IC rates, the observation group also demonstrated higher than the control group (51.8% vs. 21.4%, P = 0.002), respectively. Seven hippocampal metastases were found in the control group (4/56,7.1%) and the observation group (3/56,5.4%) after HA-WBRT. The death rate of intracranial progression were 23.2% in the observation group and 37.5% in the control group.All adverse events were not significant difference between the two groups (P>0.05). Conclusions HA-WBRT + SIB resulted in better OS,median survival, IC, iPFS, an acceptable risk of radiation response, and a potential way of declining neurocognitive adverse events, which may be a better treatment for patients with multiple brain metastases.